2010
DOI: 10.1007/s00542-010-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO nanorods on patterned templates for efficient, large-area energy scavengers

Abstract: ZnO nanostructures were grown on patterned Si substrates using a cost-efficient, low-temperature process, for their future exploitation as functional cores of nanopiezotronic applications. Different substrates and growth parameters were examined in order to determine the optimum process window that will constitute a reliable, low-cost method for large-scale ZnO nanorod production. Statistical analysis was performed to assess the size and shape distribution of the nanorods in an effort to determine the energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…As long as the substrate surface is locally flat to promote the vertical alignment of the ZnO nanowires [91], as shown in Fig. 8(c) [91,143]. X-ray diffraction studies showed the as-deposited polycrystalline Au thin films were <111> oriented normal to the substrate, even though they had random in-plane orientations [82].…”
Section: Au Coated General Substratesmentioning
confidence: 99%
“…As long as the substrate surface is locally flat to promote the vertical alignment of the ZnO nanowires [91], as shown in Fig. 8(c) [91,143]. X-ray diffraction studies showed the as-deposited polycrystalline Au thin films were <111> oriented normal to the substrate, even though they had random in-plane orientations [82].…”
Section: Au Coated General Substratesmentioning
confidence: 99%
“…For example, Niarchos et al used an alternative aqueous chemical growth (ACG) process to investigate a reliable and low-cost method, and they could grow large-scale ZnO nanorods on patterned Si substrates by a low-temperature process. (8) Li et al used Zn foil and an aqueous Na 2 C 2 O 4 solution to successfully synthesize ultralong ZnO nanowires by a simple hydrothermal reaction at 140 °C. (9) They also found that the grown ZnO nanowires could be used as sensors for NH 3 and N(C 2 H 5 ) 3 vapors, and showed excellent response characteristics towards low concentrations of NH 3 and N(C 2 H 5 ) 3 vapors.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed methodology is fully compatible with mainstream microfabrication techniques, and has thus the potential for fast laboratory-to-market times and easy transfer to mass-production. It has at its core the hydrothermal growth of ZnO nanostructures, which is a very versatile method allowing the control of the morphological characteristics of the nanostructures through tuning of simple key environmental parameters [ 27 , 28 , 29 ]. In addition, this method is facile, rapid, of extremely low cost and can be applied to a variety of substrates ranging from conventional Si wafers to flexible substrates such as Kapton [ 30 ], PDMS (poly(dimethylsiloxane)) [ 31 ], and PET (polyethylene terephthalate) [ 32 ]) as well as less conventional materials such as wood [ 33 ], paper [ 34 ], and textiles [ 35 ].…”
Section: Introductionmentioning
confidence: 99%